Pendampingan Berbagai Macam Kegiatan Posyandu di RW 011 Pada Batita Maupun Balita - Solah Abdul Razak; Tiara Amda Meilika; Mardiani Puji Lestari; Qurratuaini Zhafirah; Andini Febriyani; Muhammad Arief Effendi; Iis Nur Romadhona; Muhsin Asrul; Rizky Fauzi; Andhika Nugraha; Tengku Abdurrahman Rajak; Kresna Deska Adji; Risma Wati; Meilinda Ika Dewi (Institut Nalanda, 2024)
Posyandu is a basic health activity organized from, by and for the community assisted by health workers. The definition of Posyandu is also a forum for health care carried out from, by and for the community, guided by related officers. Posyandu is a center for community activities in the effort to provide health services and family planning. This routine activity carried out in RW 011 is able to check up to 30 toddlers and toddlers each month and even more. The results of the identification of problems faced by partners are that there are still many lack of parents who are on time in checking their children to the nearest posyandu. The implementation method is by uniting the posyandu in RW 011 so that they can make routine inspections.